Ultisols from Andesitic Volcanic Materials: the Differentiation in Fertility and Management Potential - BAMBANG HENDRO PRASETYO; DJAJA SUBARDJA; B. KASLAN (Jurnal Tanah dan Iklim (Indonesian Soil and Climate Journal), 2005)
Ultisols from andesitic volcanic material in lower slope of Mt. Ungaran are different from other Ultisols, especially in their exchangeable aluminum content, P nutrient status (retention and available P), and mineralogy of sand fraction which is dominated by opaque mineral. Interpretation results of physical, chemical, and mineralogical data from six representative soil profiles inform that Ultisols in the reconnaissance map of Central Java consist of three groups: (1) Oxisols (pedons P1 and P2) due to their clay CEC of < 16 cmolc kg-1, even though the soil structure is angular blocky, (2) Ultisols (pedons P3, P4, and P5), and (3) transition from Inceptisols to Ultisols (pedon P6) due to the unclear argillic horizon and broad form of x-ray diffraction pattern. Domination of opaque mineral indicates that nutrient retention is low for a long time. Exchangeable aluminum in the first and second group are very low and not detectable, except in the third group. Available P in the first group is moderate, while in the second group is low (P3 and P5) and high in P4. This condition indicates that theavailable P is influenced not only by aluminum but also by other factors needed to be further studied. Low available P in the third group is due to fixation of P by aluminum. Based on the soil fertility characteristics, mineralogy, and pedogenesis of every group, development of tree crops (such as rubber) in the second group should consider to overcome clay accumulation (or argilic horizon) which may constrain root development. The first group needs addition of organic matter to increase nutrient retention and improve soil stucture.